THE SPECIFICITY OF PHYSICAL TRAINING OF ATHLETES,I.E., FUTURE SPECIALISTS IN PHYSICAL CULTURE (Academia Science Repository, 2023)
The article presents the results of the analysis of scientific and methodological literature, pedagogical observationand conversation.